Mathematical Models and Immune Cell Biology 2011
DOI: 10.1007/978-1-4419-7725-0_14
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Peripheral Regulatory and Effector T Cells Competing for Antigen Presenting Cells

Abstract: A healthy immune system requires a balance between effector T (T E ) cells that mount immune responses, and regulatory T (T R ) cells that prevent them. Understanding this balance requires knowing how the repertoires of T E and T R cells in the periphery are patterned and related to each other. The present work addresses this issue in the framework of the Crossregulation model, which was formulated to contemplate the dynamics of a large number of T cell clones recognizing a non-exclusive set of antigen-present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Given the high combinatorial nature of the genetic rearrangement mechanism encoding the T-cell receptor, these new clones should exhibit different antigen specificities from the ones already existing in the periphery. Interestingly, early work using a more complex cross-regulation model demonstrated that most of the clonal selection shaping the T-cell repertoire occurs early in life (21). After this time period, the resulting T-cell repertoire is enriched with resident clones at sufficiently high density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high combinatorial nature of the genetic rearrangement mechanism encoding the T-cell receptor, these new clones should exhibit different antigen specificities from the ones already existing in the periphery. Interestingly, early work using a more complex cross-regulation model demonstrated that most of the clonal selection shaping the T-cell repertoire occurs early in life (21). After this time period, the resulting T-cell repertoire is enriched with resident clones at sufficiently high density.…”
Section: Discussionmentioning
confidence: 99%
“…Independence between clones in the repertoire simplifies the analysis as one only needs to interpret all possible dynamics of a single clone associated with a given set of cAPC. This implies that Tregs and Teffs from the same clone cross-regulate each other, but the same cells from different clones do not; a model assuming a cross-regulation between distinct clones can be found elsewhere (21).…”
Section: The Cross-regulation Model For Cd4+ T-cell Dynamics and Its mentioning
confidence: 99%